PENGUATAN AL ISLAM DAN KEMUHAMMADIYAHAN DENGAN APLIKASI KADER-MU - Mahasri Shobahiya; Nurul Latifatul Inayati; Rahma Ayuningtyas Fachrunisa; Diah Priyawati; Mirzam Arqy Ahmadi; Novel Idris Abas; Yusfina Sekar Qudsiyah; Lentera Tazkiya Ismail (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Advances in digital technology have had a significant impact on various aspects of life, including the spread of religious teachings. 'Aisyiyah Branch (PRA) Joyosuran faces challenges in the cadre and members' understanding of compulsory worship in accordance with Tarjih Muhammadiyah. This service program aims to improve 'Aisyiyah members' understanding of compulsory worship through workshops and the use of the Kader-Mu digital application. The methods used include Focus Group Discussion (FGD), workshop and practice, and evaluation using pretest and posttest. The results obtained showed an increase in members' understanding after participating in the activity, with an increase in the average pretest score of 84 to 95 in the posttest. Statistical evaluation through paired t-test showed a significant increase in members' understanding of Al Islam and Kemuhammadiyahan. Thus, this program makes a real contribution in supporting digital da'wah and strengthening regeneration in the 'Aisyiyah environment, especially for the Joyosuran branch.